An integrated phylogenetic reassessment of the parasitoid superfamily Platygastroidea (Hymenoptera: Proctotrupomorpha) results in a revised familial classification. (13th September 2021) - Chen, Huayan; Lahey, Zachary; Talamas, Elijah J.; Valerio, Alejandro A.; Popovici, Ovidiu A.; Musetti, Luciana; Klompen, Hans; Polaszek, Andrew; Masner, Lubomír; Austin, Andrew D.; Johnson, Norman F.
Abstract: The superfamily Platygastroidea (Hymenoptera: Proctotrupomorpha) is a diverse group of parasitoid wasps that are parasitoids of nine orders of insects as well as spiders. They appear to show a clear pattern of host group specificity among genera. A robust phylogeny is essential for devising a stable and informative classification and understanding the pattern of the shifts to parasitize new host groups. We conducted phylogenetic analyses of Platygastroidea based on four molecular markers ( 18S, 28S, COI and wingless ) and 119 morphological characters, and a phylogenomic analysis of a subset of taxa based on 4371 single‐copy, protein‐coding genes. The four‐gene analyses, both with and without morphological data, robustly recovered some well‐established groups, e.g., Platygastridae (in its traditional sense), Scelionini, Teleasinae and Telenominae, as well as some novel patterns of relationship. The ground‐plan host for the superfamily are the eggs of Orthoptera, with multiple shifts to attack new host groups. The phylogenomic analysis of a subset of taxa recovered a clear pattern of relationships for the backbone of the superfamily with maximal bootstrap support. Based on the combination of these two approaches, we present a revised classification for Platygastroidea and recognize the following eight families: Geoscelionidae stat.rev., Janzenellidae fam.nov., Neuroscelionidae fam.nov., Nixoniidae stat.rev., Platygastridae stat.rev., Proterosceliopsidae†, Scelionidae stat.rev. and Sparasionidae stat.rev. This published work has been registered on ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:480936B5‐3C2C‐4B6A‐B273‐10DCBF9005E9 . Abstract : We use a combination of morphological, multi‐locus Sanger sequencing, and whole‐genome sequences to infer the phylogeny of the parasitoid wasp superfamily Platygastroidea. The ancestral hosts of platygastroids were the eggs of Orthoptera. Numerous subsequent host shifts have led to the use of other hosts from an additional eight insect orders and spiders. A reclassification of the superfamily is proposed in which eight families are recognized, including the traditional families Scelionidae and Platygastridae.